Mathematical modeling of the gasdynamic charcteristics of the heat-transfer medium jet in a process of the thermal reaming of the borehole - Voloshyn, O.I.; Potapchuk, I.Yu.; Zhevzhyk, O.V.; Yemelianenko, V.I.; Teplyi, V.P.; Kholyavchenko, L.T.; Shniakin, S.V. (Геотехнічна механіка, 2017)
Purpose of the work is to develop a mathematical model for calculation of gasdynamic characteristics (pressure, density, speed) of the heat-transfer medium at its movement along the surface of the borehole in the process of its thermal reaming. For this purpose, technique and algorithm were developed for calculation of gas-dynamic characteristics of the free and semibounded jet of the heat-transfer medium at its movement along the surface of the borehole. Метою роботи є розробка математичної моделі розрахунку газодинамічних характеристик (тиск, густина, швидкість руху) теплоносія при його русі вздовж поверхні свердловини в процесі її термічного розширення. Для цього розроблено методику та алгоритм розрахунку газодинамічних характеристик вільної та напівобмеженої струмини теплоносія при його русі вздовж поверхні свердловини. Целью работы является разработка математической модели расчета газодинамических характеристик (давление, плотность, скорость движения) теплоносителя при его движении вдоль поверхности скважины в процессе ее термического расширения. Для этого разработана методика и алгоритм расчета газодинамических характеристик свободной и полуограниченной струи теплоносителя при его движении вдоль поверхности скважины.